Effects of β-cooling rates on microstructural characteristics and hardness variation of a dual-phase Zr alloy. (November 2021) - Wang, Yueyuan; Chai, Linjiang; Zhang, Fangli; Chen, Ke; Guan, Haotian; Luo, Jinru; Li, Yuqiong
Abstract: In this study, a typical dual-phase Zr alloy (Zr-2.5Nb) was subjected to β-solution treatment at 1000°C for 10 min and then cooled down to room temperature at different rates (in water (WC), air (AC) and furnace (FC)). Microstructural characteristics of the specimens were thoroughly analyzed by jointly using electron backscatter diffraction (EBSD), electron channeling contrast (ECC) imaging, X-ray diffraction (XRD) techniques and transmission electron microscopy (TEM). Specimen hardnesses were measured by a Vickers indentation tester and well correlated with the revealed microstructural characteristics. Results show that the initial dual-phase microstructure is replaced by twinned martensite, basket-weave structure and lenticular Widmanstätten structure after water cooling, air cooling and furnace cooling, respectively. Internal twins in the WC specimen are determined to be 10 1 ¯ 1 compressive twinning, while inter-plate films in AC and FC specimens are Nb-enriched residual β phases. Orientation analyses show that the α phase exhibits the Burgers misorientation characteristics in all the β-cooled specimens and a single β orientation can give birth to all 12 α variants at relatively high cooling rates (both in water and air). Hardness analyses reveal that faster cooling always results in higher hardness, increasing from 216.5 HV of the FC specimen to 285.9 HV of the WC specimen (harder than the as-received material (221.9 HV)). Such variation is related to hardening contributions from specific microstructural (grain refinement, nanotwins, and solid solution) and orientation characteristics (angles between c-axes of α grains and the loading direction). Highlights: Microstructures of Zr-2.5Nb β-cooled in different ways are revealed by multiple characterization methods. Twinned martensite, basket-weave and lenticular Widmanstätten structures present after WC, AC and FC. A single β orientation can give birth to all 12 α variants at relatively high cooling rates (WC and AC). Faster cooling results in higher hardness, increasing from 216.5 HV (FC) to 285.9 HV (WC). Hardening contributions from specific microstructural and orientation characteristics are revealed.